The Influence of Job Insecurity and Workload on the Turnover Intention of Generation Z Employees in Bima City - Syrilus Alexander Alvaro Roja; Jaenab Jaenab; Rahmatia Rahmatia (Devitara Innovations, 2024)
The purpose of this study was to examine the effect of job insecurity and workload on turnover intention of generation Z employees in Bima City. This research is quantitative research and the type of research is associative. The population in this study amounted to 100 generation Z employees and the sampling technique used incidental sampling. Data collection techniques using a questionnaire, with reference to a 5-point Likert scale then distributed to 100 respondents on generation Z employees in Bima City. Data analysis was carried out through validity test, reliability test, classical assumption test, multiple linear regression, correlation coefficient, coefficient of determination, t test, and F test with the help of SPSS version 25 for windows. The results of this study 1) There is no significant effect of job insecurity on turnover intention of generation Z employees of Bima City. 2) There is a significant influence of workload on the turnover intention of generation Z employees in Bima City. 3) There is a significant influence of job insecurity and workload on the turnover intention of generation Z employees in Bima City.